Unipampa campus São Borja: como o receptor representa a instituição através da comunicação Institucional - (:unkn) unknown (Universidade Federal do Pampa, 2015)
This paper aims to study how students of the third year of high school in São Borja and their parents or guardians build the representation of the Federal University of Pampa (UNIPAMPA) Campus San Borja by communicating it produces. For this it was necessary a review of cultural studies and the Paradigm Culturológico, chronologically to understand how is the relationship between communication and culture. To account for this complexity are addressed the concepts of Communication Policies, Institutional Communication and Communication consultants, Federal University of Pampa and its Advisory and target audience and their historical and sociocultural context. The analysis start using the interview method in depth which is organized from the perspective of Map of mediations of Barbero (2006) - using in all the work as a theoretical and methodological support. The map allows the coordination, according to the perspectives of cultural studies, Logical production and other techniques used in Corporate Communications established by UNIPAMPA, the Industrial Formats, to know the means, tools, platforms, messaging and content produced by the Institution . Guides the understanding of the rituals of consumption for this target audience, which comes from Reception Skills and thereby understand how live and socialize in society to understand the cultural matrices that influence the formation of opinion of individuals and how they manage São Borja represent the campus of the Federal University of Pampa. With the interviews you can see who are the social, cultural, political and economic factors that help form the identity of these individuals and their formation of opinion, and that influence in how they can represent the UNIPAMPA by what they hear, read and They see it on third parties such as friends, co-workers and class, neighbors, and others which live in society, including communication established by the University.
Keywords: Comunicação; Comunicação na administração pública; Universidade Federal do Pampa; Estudos culturais; Communication; Cultural studies; CNPQ::CIENCIAS SOCIAIS APLICADAS